Impacto do tamanho de parcelas na resposta de genótipos de cana-de-açúcar às ferrugens marrom e alaranjada em experimentos de campo - Almeida, Lucas Porphirio de (Universidade Federal de São Carlos, 2022)
Among the diseases that cause damage to the sugarcane crop, two of the most important are brown rust, caused by the fungus Puccinia melanocephala, and orange rust, caused by the fungus P. kuehnii. Both affect the leaf blade of plants, reducing their photosynthetic rate, which can lead to large losses if not effectively controlled. The most efficient way to controlling sugarcane rust is through the use of resistant varieties, obtained through research carried out by genetic improvement programs. This study aimed to evaluate the impact of reducing the size of plots on the response of sugarcane genotypes to brown and orange rusts in field experiments. Two experiments were carried out in the city of Macaws, in the State of São Paulo, and the plots of Experiment 1 were composed of two 2.5 m long furrows, while in Experiment 2 they were laid down with a furrow of 2.5 m. To increase inoculum pressure in areas experimental, in both tests the variety SP89-1115, susceptible to orange, was planted as a border and between the blocks, and the variety RB835486, susceptible to brown rust, was planted as an infective line every six furrows. The severity of both diseases was evaluated every 15 days, until stabilization. of symptoms. With the data obtained, the areas below the curves were calculated disease progress and the maximum severity score was determined for each rust in each genotype. The reaction of genotypes to rust was not impacted by reducing the size of experimental plots; so it is convenient to decrease, which will allow the evaluation of more genotypes without increasing the experimental area, as long as the design used in this study was followed.
Impact of the size of installments on the response of sugarcane genotypes to brown rust and orange in field experiments
Keywords: Saccharum spp.; Puccinia melanocephala; Puccinia kuehnii; Delineamento experimental; Melhoramento genético; Experimental design; Genetic improvement; CIENCIAS AGRARIAS